Implementasi MSP Kerja Sama Akreditasi Halal antara ESMA dan KAN Tahun 2018 - Suci Indah Lestari; Agus Hadiawan; Tety Rachmawati (Bukhori: Kajian Ekonomi dan Keuangan Islam, 2022)
Purpose: To analyze implementation of a Memorandum of Understanding (MoU) in the field of cooperation halal accreditation between the National Accreditation Committee (KAN) and Emirates Authority for Standardization and Metrology (ESMA) 2018 in trade relations between Indonesia and the UAE. Method: This type of research is descriptive qualitative using secondary data. The data collection technique used document analysis while the data analysis technique used content analysis which refers to the process of classifying, summarizing and tabulating data. Result: The results of this study are all 6 MoU mechanisms in halal accreditation cooperation have been carried out according to mutually agreed procedures and an understanding of halal accreditation. It has been reached through LSH Indonesia which is recognized by ESMA. However, the implementation of the MoU has not provided a maximum contribution yet to Indonesia's trade relations with the UAE.